Novel mRNA vaccines induce potent immunogenicity and afford protection against tuberculosis - De Voss, Christopher J.; Korompis, Marcellus; Li, Shuailin; Ateere, Alberta; McShane, Helen; Stylianou, Elena (Frontiers in Immunology, 2025)
IntroductionMycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB), a disease with a severe global burden. The intractability of Mtb has prevented the identification of clear correlates of protection against TB and hindered the development of novel TB vaccines that are urgently required. Lipid nanoparticle (LNP)-formulated mRNA is a highly promising vaccine platform that has yet to be thoroughly applied to TB.MethodsWe selected five Mtb antigens (PPE15, ESAT6, EspC, EsxI, MetE) and evaluated their potential as LNP-formulated mRNA vaccines, both when each antigen was delivered individually, and when all five antigens were combined in a mix regimen (m-Mix).ResultsEach mRNA construct demonstrated unique cellular and humoral immunogenicity, and both m-Mix, as well as the single antigen EsxI, conferred significant protection in a murine Mtb challenge model. Whilst the potent immune responses of each mRNA were maintained when applied as a boost to BCG, there was no additional increase to the efficacy of BCG. Combination of m-Mix with a recombinant, replication-deficient chimpanzee adenovirus (ChAdOx1), in a heterologous prime-boost delivery (C-m-Mix), appeared to result in increased protection upon murine Mtb infection, than either regimen alone.DiscussionThis work warrants further investigation of LNP-formulated mRNA vaccines for TB, whilst indicating the potential of m-Mix and C-m-Mix to progress to further stages of vaccine development.